1995
DOI: 10.1016/1074-7613(95)90178-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct presentation of nonpeptide prenyl pyrophosphate antigens to human γδ T cells

Abstract: Human V gamma 2V delta 2+ T cells recognize mycobacterial nonpeptide antigens, such as isopentenyl pyrophosphate, and their synthetic analogs, such as monoethyl phosphate, through a TCR-dependent process. Here, we examine the presentation of these antigens. V gamma 2V delta 2+ T cells recognized secreted prenyl pyrophosphate antigens in the absence of other accessory cells but, under such conditions, required T cell-T cell contact. Recognition required neither the expression of classical MHC class I, MHC class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
387
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 433 publications
(404 citation statements)
references
References 73 publications
14
387
2
1
Order By: Relevance
“…In the mouse, cd T cell subsets recognize the non-classical MHC class I molecules T10/T22 [15], and an unknown ligand expressed by keratinocytes [16]. In humans, some Vd1 cd T cells recognize non-classical MHC class I molecules MICA and MICB, and Vc9Vd2 cd T cells have been reported to recognize self and bacterial phosphoantigens, and a complex formed between F1-ATP synthase and apolipoprotein A-1 [5,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse, cd T cell subsets recognize the non-classical MHC class I molecules T10/T22 [15], and an unknown ligand expressed by keratinocytes [16]. In humans, some Vd1 cd T cells recognize non-classical MHC class I molecules MICA and MICB, and Vc9Vd2 cd T cells have been reported to recognize self and bacterial phosphoantigens, and a complex formed between F1-ATP synthase and apolipoprotein A-1 [5,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, cd T cell subsets recognize the non-classical MHC class I molecules T10/T22 [15], and an unknown ligand expressed by keratinocytes [16]. In humans, some Vd1 cd T cells recognize non-classical MHC class I molecules MICA and MICB, and Vc9Vd2 cd T cells have been reported to recognize self and bacterial phosphoantigens, and a complex formed between F1-ATP synthase and apolipoprotein A-1 [5,[17][18][19][20].During mouse NK cell development, lineage markernegative bone marrow progenitors develop progressively into CD122 + NK1.1 -DX5 -committed NK progenitors, CD122 + NK1.1 + DX5 -immature NK cells and finally CD122 + NK1.1 + DX5 + mature NK cells, all of which can be found in the bone marrow. At the immature DX5 -stage, NK cells express multiple NK receptors including CD94/NKG2, NKG2D and NKp46, but are unable to perform granule-mediated cytotoxicity [21][22][23].…”
mentioning
confidence: 99%
“…These phosphoantigens are usually natural metabolites of isoprenoid biosynthesis in host cells, which include IPP, (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate, dimethylallyl pyrophosphate (DMAPP) 53,54 and bromohydrin pyrophosphate. 55 These phosphoantigens can be presented by T cells, monocytes and various antigen-presenting cells (APCs), such as DCs and B cells, 56,57 through expression of CD1d 58,59 and as-yet unknown non-MHC molecules on host cells. 60 The clinical applications of phosphoantigens in cd-T cell-based therapy will be discussed in a later part of this review.…”
Section: Host Cell-derived Signalsmentioning
confidence: 99%
“…However, in some cases it has been shown that Ags must be presented to be stimulatory for cd T cells. 17 These presented Ags tend to be small, and in soluble form might not be capable of TCR cross-linking, a prerequisite for activation via immunoreceptors. Whether any Ags in solution can be recognized and can trigger responses of cd T cells is not yet known, although this seems likely when such Ags are multivalent.…”
Section: Mechanism Of Ligand Recognitionmentioning
confidence: 99%
“…105 This may be more understandable considering that these small molecules appear to be presented on the surface of target cells 17,106,107 and thus might be 'seen' in a certain context. However, the mechanism of presentation remains mostly unclear, and it might vary between individual Ags.…”
Section: Non-peptidic Agsmentioning
confidence: 99%